Regulation of adult stem cell behavior by nutrient signaling. - Wang, L.; McLeod, C.; Jones, D.L. (Cell Cycle, 2011)
Adult stem cells play an essential role?throughout life, maintaining tissue and organ function by providing a reservoir of cells for homeostasis and repair. Maintenance and activity of adult stem cells have been the focus of numerous studies that have revealed stem cell-intrinsic factors and signals from the local microenvironment that regulate stem cell behavior. A growing body of work has provided evidence that circulating, systemic factors also contribute to the regulation of stem cell behavior in numerous tissues. We have demonstrated that Drosophila male germline stem cells (GSCs) and intestinal stem cells (ISCs) respond to changes in nutrient availability, specifically amino acids. Furthermore, we have shown that insulin signaling plays an important role in mediating the effects of changes in nutritional conditions. Notably, insulin signaling is cell-autonomously required within male GSCs for maintenance. Here we discuss our data regarding the effects and mechanisms by which changes in systemic nutritional conditions may influence the maintenance and activity of adult stem cells via insulin signaling.